A gene expression comparison of Trypanosoma brucei and Trypanosoma congolense in the bloodstream of the mammalian host reveals species-specific adaptations to density-dependent development. - Eleanor Silvester; Alasdair Ivens; Keith R Matthews (Public Library of Science (PLoS), 2018)
In the bloodstream of mammalian hosts Trypanosoma brucei undergoes well-characterised density-dependent growth control and developmental adaptation for transmission. This involves the differentiation from proliferative, morphologically 'slender' forms to quiescent 'stumpy' forms that preferentially infect the tsetse fly vector. Another important livestock trypanosome, Trypanosoma congolense, also undergoes density-dependent cell-cycle arrest although this is not linked to obvious morphological transformation. Here we have compared the gene expression profile of T. brucei and T. congolense during the ascending phase of the parasitaemia and at peak parasitaemia in mice, analysing species and developmental differences between proliferating and cell-cycle arrested forms. Despite underlying conservation of their quorum sensing signalling pathway, each species exhibits distinct profiles of gene regulation when analysed by orthogroup and cell surface phylome profiling. This analysis of peak parasitaemia T. congolense provides the first molecular signatures of potential developmental competence, assisting life cycle developmental studies in these important livestock parasites. Furthermore, comparison with T. brucei identifies candidate molecules from each species that may be important for their survival in the mammalian host, transmission or distinct tropism in the tsetse vector.